Structural and electronic investigations of In2O3 nanostructures and thin films grown by molecular beam epitaxy - Zhang, H (2011)
Transparent conducting oxides (TCOs) combine optical transparency in the visible region with a high electrical conductivity. In2O3 doped with Sn (widely, but somewhat misleadingly, known as indium tin oxide or ITO) is at present the most important TCO, with applications in liquid crystal displays, touch screen displays, organic photovoltaics and other optoelectronic devices. Surprisingly, many of its fundamental properties have been the subject of controversy or have until recently remained unknown, including even the nature and magnitude of the bandgap. The technological importance of the material and the renewed interest in its basic physics prompted the research described in this thesis. This thesis aims (i) to establish conditions for the growth of high-quality In2O3 nanostructures and thin films by oxygen plasma assisted molecular beam epitaxy and (ii) to conduct comprehensive investigations on both the surface physics of this material and its structural and electronic properties. It was demonstrated that highly ordered In2O3 nanoislands, nanorods and thin films can be grown epitaxially on (100), (110) and (111) oriented Y-stabilized ZrO2 substrates respectively. The mismatch with this substrate is -1.7%, with the epilayer under tensile strain. On the basis of ab initio density functional theory calculations, it was concluded that the striking influence of substrate orientation on the distinctive growth modes was linked to the fact that the surface energy for the (111) surface is much lower than for either polar (100) or non-polar (110) surfaces. The growth of In2O3(111) thin films was further explored on Y-ZrO2(111) substrates by optimizing the growth temperature and film thickness. Very thin In2O3 epilayers (35 nm) grew pseudomorphically under high tensile strain, caused by the 1.7% lattice mismatch with the substrate. The strain was gradually relaxed with increasing film thickness. High-quality films with a low carrier concentration (5.0  1017 cm-3) and high mobility (73 cm2V-1s-1) were obtained in the thickest films (420 nm) after strain relaxation. The bandgap of the thinnest In2O3 films was around 0.1 eV smaller than that of the bulk material, due to reduction of bonding-antibonding interactions associated with lattice expansion. The high-quality surfaces of the (111) films allowed us to investigate various aspects of the surface structural and electronic properties. The atomic structure of In2O3 (111) surface was determined using a combination of scanning tunnelling microscopy, analysis of intensity/voltage curves in low energy electron diffraction and first-principles ab initio calculations. The (111) termination has an essentially bulk terminated (1 × 1) surface structure, with minor relaxations normal to the surface. Good agreement was found between the experimental surface structure and that derived from ab initio density functional theory calculations. This work emphasises the benefits of a multi-technique approach to determination of surface structure. The electronic properties of In2O3(111) surfaces were probed by synchrotron-based photoemission spectroscopy using photons with energies ranging from the ultraviolet (6 eV) to the hard X-ray regime (6000 eV) to excite the spectra. It has been shown that In2O3 is a highly covalent material, with significant hybridization between O and In orbitals in both the valence and the conduction bands. A pronounced electron accumulation layer presents itself at the surfaces of undoped In2O3 films with very low carrier concentrations, which results from the fact the charge neutrality level of In2O3 lies well above the conduction band minimum. The pronounced electron accumulation associated with a downward band bending in the near surface region creates a confining potential well, which causes the electrons in the conduction band become quantized into two subband states, as observed by angle resolved photoemission spectra (ARPES) Fermi surface mapping. The accumulation of high density of electrons near to the surface region was found to shrink the surface band gap through many body interactions. Finally epitaxial growth of In2O3 thin films on α-Al2O3(0001) substrates was investigated. Both the stable body centred cubic phase and the metastable hexagonal corundum In2O3 phase can be stabilized as epitaxial thin films, despite large mismatches with the substrate. The growth mode involves matching small but different integral multiples of lattice planes of the In2O3 and the substrate in a domain matching epitaxial growth mode.